2015
DOI: 10.3109/03639045.2015.1062896
|View full text |Cite
|
Sign up to set email alerts
|

Histological assessment of follicular delivery of flutamide by solid lipid nanoparticles: potential tool for the treatment of androgenic alopecia

Abstract: It was concluded Flutamide-loaded SLN formulation can be used as a promising colloidal drug carriers for topical administration of Flutamide in the treatment of androgenic alopecia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 45 publications
1
32
0
Order By: Relevance
“…The mean particle size of lipid nanoparticles usually depends on several factors, such as type and concentration of lipid surfactants and the viscosity in lipid phases. 4 To avoid interfering with other effective parameters in skin penetration, the total amounts of lipid phase and surfactant were kept constant. The speed of homogenizer and the process time were changed to provide three SLN formulations with distinctly different submicron particle sizes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The mean particle size of lipid nanoparticles usually depends on several factors, such as type and concentration of lipid surfactants and the viscosity in lipid phases. 4 To avoid interfering with other effective parameters in skin penetration, the total amounts of lipid phase and surfactant were kept constant. The speed of homogenizer and the process time were changed to provide three SLN formulations with distinctly different submicron particle sizes.…”
Section: Resultsmentioning
confidence: 99%
“…The images were taken from normal light and fluorescence microscope of the same area and the dye distribution in the skin was evaluated qualitatively. 4 …”
Section: Characterization Of Rhodamine B-loaded Slnmentioning
confidence: 99%
See 2 more Smart Citations
“…This result contradicts the report by Patzelt et al, who showed that reductions in particle size (643 nm, 470 nm, 300 nm, and 122 nm) led to a significant reduction in particle penetration depth. 25,26 Transportation through the skin was limited to molecules with certain properties (molecular weight < 500 Dalton, moderate lipophilicity with octanolwater partition coefficient between 10 and 1000, and melting point < 200 °C). 4,27 However, additional means is usually required to increase transportation through the skin.…”
Section: Preparation Of Naga-loaded Nlcsmentioning
confidence: 99%